Investigating the impact of feed-induced, subacute ruminal acidosis on rumen epimural transcriptome and metatranscriptome in young calves at 8- and 17-week of age - Li, Wenli; Larsen, Anna; Fregulia, Priscila (Frontiers in Veterinary Science, 2024)
With the goal to maximize intake of high-fermentable diet needed to meet energy needs during weaning period, calves are at risk for ruminal acidosis. Using the calves from previously established model of feed-induced, ruminal acidosis in young calves, we aimed to investigate the changes in rumen transcriptome and metatranscriptome of its associated microbial community at weaning (8-week) and post-weaning (17-week) in canulated (first occurred at 3 weeks of age) Holstein bull calves with feed-induced subacute ruminal acidosis. Eight bull calves were randomly assigned to acidosis-inducing (Aci, Treated, n=4; pelleted, 42.7% starch, 15.1% neutral detergent fiber [NDF], and 57.8% nonfiber carbohydrates), while texturized starter was fed as a control (Con, n=4; 35.3% starch, 25.3% NDF, and 48.1% nonfiber carbohydrates) starting at birth through 16 weeks. Calves fed acidosis inducing diet showed significantly less (P<0.01) body weight over the course of the experiment, in addition to lower ruminal pH (P < 0.01) compared to the control group. Rumen epithelial (RE) tissues were collected at both 8 weeks (via biopsy) and 17 weeks (via euthanasia) and followed for whole transcriptome RNA sequencing analysis. Differentially expressed genes (DEG) analysis was done using DEseq2 (fold-change ≥ 2 and P ≤ 0.05) between Aci and Con groups at 8-week of age, and between 8-week and 17-week for the Aci group. At 8-week of age, DEGs between treatment groups showed an enrichment of genes related to the response to lipopolysaccharide (LPS) (P<0.05). The impact of prolonged acidosis feeding was reflected by the decreased expression (P<0.005) in genes involved in cell proliferation related pathways in the RE at 17-week of age in the treated group. Unique sets of discriminant microbial taxa were identified between 8-and 17-week calves in the treated group and the treatment groups at 8-week, indicating that active microbial community changes are an integral part of the ruminal acidosis development and progression. Our findings underlined the important role of microbial communities in the development of feed-induced ruminal acidosis. And the genes related to cellular response to lipopolysaccharide might be useful tools for early diagnosis and prevention of ruminal acidosis.